2015
DOI: 10.1142/s1793545815500340
|View full text |Cite
|
Sign up to set email alerts
|

Application of near infrared spectroscopy in monitoring the moisture content in freeze-drying process of human coagulation factor VIII

Abstract: As an important process analysis tool, near infrared spectroscopy (NIRS) has been widely used in process monitoring. In the present work, the feasibility of NIRS for monitoring the moisture content of human coagulation factor VIII (FVIII) in freeze-drying process was investigated. A partial least squares regression (PLS-R) model for moisture content determination was built with 88 samples. Di®erent pre-processing methods were explored, and the best method found was standard normal variate (SNV) transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In order to improve the accuracy of model and reduce the modeling time, more and more wavenumbers selection methods were reported nowadays, such as, regression coefficient analysis (RCA) 17 , Genetic algorithm (GA) 18 and random forests (RF) 19 . In this research, a hybrid wavenumbers selection method, which combined backward interval partial least squares (biPLS) regression 20 , competitive adaptive reweighted sampling (CARS) algorithm 21 and successive projections algorithm (SPA) 22 , was applied for IR spectral wavenumbers selection.…”
mentioning
confidence: 99%
“…In order to improve the accuracy of model and reduce the modeling time, more and more wavenumbers selection methods were reported nowadays, such as, regression coefficient analysis (RCA) 17 , Genetic algorithm (GA) 18 and random forests (RF) 19 . In this research, a hybrid wavenumbers selection method, which combined backward interval partial least squares (biPLS) regression 20 , competitive adaptive reweighted sampling (CARS) algorithm 21 and successive projections algorithm (SPA) 22 , was applied for IR spectral wavenumbers selection.…”
mentioning
confidence: 99%
“…18 Prieto et al 19 concluded that pH measurement was feasible for meat products with NIRS. Wang et al 20 demonstrated the feasibility for the determination of moisture content in human coagulation factor VIII freeze-drying process with NIRS. Zhang et al 21 used NIRS to determine the IgG content in the process of alcohol precipitation, and established a quantitative analysis model.…”
Section: Introductionmentioning
confidence: 99%
“…Near infrared spectroscopy (NIRS) has the advantage of convenience, and being versatile, nondestructive, and rapid, and hence is a good process analytical technology (PAT) tool for real-time analysis and is widely used in the pharmaceutical industry. It has already shown a great application in the analysis of chemical (Islam et al, 2015) and biological medicines (Wang F. et al, 2015). When it comes to traditional Chinese medicines (TCMs), NIRS was successfully used for quantitative assays and identification (Li et al, 2016) and classification of TCMs (Wang and Yu, 2015).…”
Section: Introductionmentioning
confidence: 99%